La formación pedagógica de académicos clínicos en la Facultad de Medicina de la Universidad de Chile - Herskovic L., Pedro (Revista Hospital Clínico Universidad de Chile, 2009)
Clinical tutors live in constant tension. They must care form patients, do research, generate funds and teach. Traditionally the average clinical tutors have had no formal training for teaching. The lack of formal training impairs their ability to optimize their students learning and accept changes in the educational environment. All these factors, and maybe more, often put teaching in the last position in their list of duties. Faculty development courses have been shown to improve teaching skills and satisfaction of clinical tutors. We have been offering for the last two years this type of courses, tailored to the needs of clinical tutors, taking the courses to the hospitals where they work, and using a time slot that causes the least interference with their work schedule. Seven courses have been given, and clinical tutors seem to be making changes on how they teach.